Translocation: movement of tRNA and mRNA through the ribosome - Noller, Harry (Henry Stewart Talks, 2008)
Ribosomes and translation, Molecular composition of the ribosome, Why is the ribosome so big?, The mRNA channel in the 30S subunit, Positions of tRNA in the A-, P- and E-sites, Structural dynamics of the ribosome during translocation, The hybrid states elongation cycle, tRNA binding during its movement through the ribosome, The 70S ribosome, Distortion of tRNA structure by the ribosome, The ratchet model, Cryo-EM experiment, Inferred relationship between ratcheting and hybrid states, FRET changes, Intersubunit movement, Testing the ratchet model for translocation, Translocation assay, What defines the mechanism of translocation, Sparsomycin, The energetics of translocation, E-site tRNA, The ribosome is a molecular machine